DDRE-22. TARGETING SERINE SYNTHESIS IN BRAIN METASTASIS. (25th March 2021) - Ngo, Bryan; Kim, Eugenie; Osorio-Vasquez, Victoria; Doll, Sophia; Bustraan, Sophia; Liang, Roger; Luengo, Alba; Davidson, Shawn; Ali, Ahmed; Ferraro, Gino; Fischer, Grant; Plasger, Ariana; et al.
Abstract: The brain environment is low in amino acids, including serine and glycine, both of which are important for tumor growth as they are precursors of proteins and nucleotide bases. How tumor cells overcome these conditions to proliferate and survive in the brain is incompletely understood. Here, we show that 3-phosphoglycerate dehydrogenase (PHGDH), which catalyzes the first and rate-limiting step of glucose-derived serine synthesis, enables brain metastasis in multiple human types and in preclinical models. Genetic suppression and small molecule inhibition of PHGDH attenuated brain metastasis, but not extra cranial tumors, and improved the overall survival of mice bearing brain metastasis. These results demonstrate that the tumor nutrient microenvironment determines tumor cell sensitivity to loss of serine synthesis pathway activity and raise the possibility that serine synthesis inhibitors may be useful in the treatment of brain metastases.